Pengaruh Kejelasan Sasaran Anggaran Dan Pengendalian Akuntansi Terhadap Akuntabilitas Kinerja Pada Dinas Perindustrian, Perdagangan Energi Dan Sumber Daya Mineral Provinsi Sumatera Utara - Elsa Pinika Putri Purba; Kusmilawaty Kusmilawaty (Akuntansi, 2024)
This research aims to determine the effect of clarity of budget targets, accounting control, on the accountability of government agency performance in the North Sumatra Industry, Energy Trade and Mineral Resources Department. This research uses quantitative methods with an associative approach, data collection techniques using questionnaires and the population and sample in this research are the entire office apparatus organization and heads of sections/Departments of Industry, Energy Trade and Mineral Resources of North Sumatra Province consisting of the Finance Sub-Section, Head of the Program and Planning Sub-Division, as many as 30 employees with a sampling technique using saturated sampling technique. Data were analyzed using multiple linear regression methods. The results of the partial test hypothesis show that Clarity of Budget Targets has a positive effect on the Performance Accountability of Government Agencies of the Department of Industry, Energy Trade and Mineral Resources of North Sumatra Province, while Accounting Control has no effect on the Performance Accountability of Government Agencies of the Department of Industry, Energy Trade and Mineral Resources of Sumatra Province North.